Enhancing Higher Order Question of Student Through Problem Based Learning at Grade X MIA 6 of SMA N 4 Surakarta - Erwin Sulistianti; Atika Guritna Ayu; Sajidan Sajidan; Sri Widoretno; Murni Ramli; Joko Ariyanto (Universitas Sebelas Maret, 2015)
The research aims to enhance the Higher Order Question of student through problem based learning in Biology at Grade X MIA 6 of SMA N 4 Surakarta. The research was a four-cycle action research conducted in academic year 2014/2015. All questions were analyzed based on revised Bloom Taxonomy. Data were validated using triangulation method. The result of the research showed that problem based learning effectively enhance student’s High Order Question (C4-C6). The percentage of each High Order Question (C4-C6) in pre cycle were 0%. The percentage of C4 type question at first cycle (73,14%), second cycle (52,13%), third cycle (56,05%), and fourth cycle (58,42%). The percentage of each High Order Question (C4-C6) in pre cycle were 0%. The percentage of C5 type question at first cycle (18,37%), second cycle (9,57%), third cycle (10,30%), and fourth cycle (58,42%). The percentage of each High Order Question (C4-C6) in pre cycle were 0%. The percentage of C6 type question at first cycle (8,16%), second cycle (38,30%), third cycle (41,18%) and fourth cycle (25,74%).Keywords: problem based learning, Higher Order Question